VO #032 Valuation of embedded parts and junction box for MEP works (Rev. 04) - BUCG-ABC Joint Venture (Brac University, 2023)
This record consists of general correspondence regarding VO #032 valuation of embedded parts and junction box for MEP works (Rev. 04) of BRAC University new campus project.